Measuring Contract Agency Performance with Administrative Data - Wulczyn, Fred; Orlebeke, Britany; Melamid, Elan (Child welfare, 2000)
This article uses administrative data to analyze the relative performance of contract agencies—those organizations under contract with a city child welfare agency to provide out-of-home care services to children placed in the custody of the public agency—by examining how long it took children placed in out-of-home care to return home to their families. The objective was to determine whether credible empirical evidence could show a relationship between length of stay and the agency providing care. Agency level reunification rates are widely distributed around the mean, indicating that contract agency performance differs and that "agency effects" leave an independent imprint on a child's out-of-home care experience.